Strategi Bertahan Dan Modal Sosial Pedagang Pasar Tradisional Swasta Dalam Perspektif Ekonomi Islam - Lia Istifhama (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
Lifestyle shift as a consequence of modernization applied in many ways, one of them consuming habits. In this case, the community is increasingly being entertained by a variety of modern shopping that presents a more comfortable atmosphere than traditional markets and variants offer discounted prices. Competition between modern retail through price competition and certain events even makes the traditional market increasingly lagging behind. In fact, the traditional market is a mirror of the people's business sector trade because it involves micro-scale traders. In order to maintain the existence of the real sector, of course, special efforts are needed to save or maintain its existence. These efforts can involve the government through market revitalization or policies that are pro poor budgeting, or strengthening marketing strategies by the traders themselves. During this time most traders familiar with marketing in conventional angle alone, whereas as knowledge of Islamization, marketing can also be applied according to Islamic concepts. In addition to marketing that can be an important point in survival strategies, social capital is certainly able to sustain so that people's business sector can still stand normal in the middle of modern retail growth.